Heterologous assembly and rescue of stranded phycocyanin subunits by expression of a foreign cpcBA operon in Synechocystis sp. strain 6803. - Plank, T (1995)
Light harvesting in cyanobacteria is performed by the biliproteins, which are organized into membrane-associated complexes called phycobilisomes. Most phycobilisomes have a core substructure that is composed of the allophycocyanin biliproteins and is energetically linked to chlorophyll in the photosynthetic membrane. Rod substructures are attached to the phycobilisome cores and contain phycocyanin and sometimes phycoerythrin. The different biliproteins have discrete absorbance and fluorescence maxima that overlap in an energy transfer pathway that terminates with chlorophyll. A phycocyanin-minus mutant in the cyanobacterium Synechocystis sp. strain 6803 (strain 4R) has been shown to have a nonsense mutation in the cpcB gene encoding the phycocyanin beta subunit. We have expressed a foreign phycocyanin operon from Synechocystis sp. strain 6701 in the 4R strain and complemented the phycocyanin-minus phenotype. Complementation occurs because the foreign phycocyanin alpha and beta subunits assemble with endogenous phycobilisome components. The phycocyanin alpha subunit that is normally absent in the 4R strain can be rescued by heterologous assembly as well. Expression of the Synechocystis sp. strain 6701 cpcBA operon in the wild-type Synechocystis sp. strain 6803 was also examined and showed that the foreign phycocyanin can compete with the endogenous protein for assembly into phycobilisomes.